Foundations and practice of security : 8th International Symposium, FPS 2015, Clermont-Ferrand, France, October 26-28, 2015. Revised selected papers /: 8th International Symposium, FPS 2015, Clermont-Ferrand, France, October 26-28, 2015. Revised selected papers. (2016) - Unknown
No abstract available